SMEs: How to Make a Successful Transition From Conventional Training Towards e-Learning - Roy, Andrée (International Journal of Advanced Corporate Learning (iJAC), 2010)
The purpose of this study is to define what e-Learning consists of, its characteristics and the various barriers to it for SMEs and to verify, through a multiple case study, the extent to which Atlantic Canadian SMEs face the same barriers than larger organizations when they want to use e-Learning. The purpose of the study is also to present the different approaches, such as determine an overall learning strategy, develop a culture more conducive to e-Learning and upgrade the technological skills of the employees, that small and medium-sized businesses can use if they want to make a successful transition from traditional training to e-Learning to train their employees.